Optimasi Formula Tablet Ekstrak Daun Salam (Eugenia Polyanthawight.) Dengan Bahan Penghancur Natrium Alginat Dan Bahan Pengikat Gelatin Menggunakan Metode Simplex Lattice Design - Rahmawati, Ana Sholi, Erindyah Retno Wikantyasning, Ph.D., Apt (2016)
Salam (Eugenia polyantha Wight.) contain flavonoid quercitrin group efficacious as analgesic. Quercitrin inhibit prostaglandin in inflamatory processes. Beside the active ingredient required material like filler, binder, disintegrant, and lubricant material. This study is used gelatin as a binder and sodium alginate as disintegrant. The purpose of obtaining formula preparation (Eugenia polyantha Wight.) tablets steady by comparison concentration gelatin and sodium alginate particular. The optimization used a Design Expert Simplex Lattice Design (SLD). This research using 8 the formula F I (8% Gelatin:4% Sodium Alginate), F II (8% Gelatin:4% Sodium Alginate), F III (7% Gelatin:5% Sodium Alginate), F IV 6% Gelatin:6% Sodium Alginate), F V (6% Gelatin:6% Sodium Alginate), F VI (5% Gelatin:7% Sodium Alginate), F VII (4% Gelatin: 8% Sodium Alginate), F VIII (4% Gelatin:8% Sodium Alginate). Test conducted is fluidity tester, silence angular, tapped density test, uniformity of weight,hardnes test, friability test, and disintegrant time. Analyzed with Design Expert 9.0.2.0. The result showed on the Design Expert 9.0.2.0, obtained formula steady in combination gelatin 4% and sodium alginate 8% with the desirability 0,717.The result for each parameter is fluidity test 15,99 grams per second + 1,46, silence angular test 34,940 + 1,76, tapped density test 7,7% + 1,2 uniformity of wight 0,59% + 0,11, hardnes test 4,3 kg + 0,8, friability test 0,387% + 0,120, dan disintegrant time 16 menit + 1,9.